Effects of drought and salt-stresses on gene expression in Caragana korshinskii seedlings revealed by RNA-seq. (December 2016) - Li, Shaofeng; Fan, Chengming; Li, Yan; Zhang, Jianhui; Sun, Jingshuang; Chen, Yuhong; Tian, Changyan; Su, Xiaohua; Lu, Mengzhu; Liang, Chengzhi; Hu, Zanmin
Abstract Background Drought and soil salinity are major abiotic stresses. The mechanisms of stress tolerance have been studied extensively in model plants.Caragana korshinskii is characterized by high drought and salt tolerance in northwestern China; unique patterns of gene expression allow it to tolerate the stress imposed by dehydration and semi-desert saline soil. There have, however, been no reports on the differences betweenC. korshinskii and model plants in the mechanisms underlying their drought and salt tolerance and regulation of gene expression. Results Three sequencing libraries from drought and salt-treated whole-seedling- plants and the control were sequenced to investigate changes in theC. korshinskii transcriptome in response to drought and salt stresses. Of the 129, 451 contigs, 70, 662 (54.12 %) were annotated with gene descriptions, gene ontology (GO) terms, and metabolic pathways, with a cut-off E-value of 10−5 . These annotations included 56 GO terms, 148 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, and 25 Clusters of Orthologous Groups (COG). On comparison of the transcriptomes of the control, drought- and salt-treated plants, 1630 and 1521 contigs showed significant differences in transcript abundance under drought and salt stresses. Compared to the differentially expressed genes (DEGs) in drought- or salt-treatedArabidopsis in the database, 542 DEGs in drought-treatedC. korshinskii and 529 DEGs in salt-treated samples were presumably unique toC. korshinskii . The transcription profiles revealed that genes related to transcription factors, protein kinases, and antioxidant enzymes are relevant to the tolerance of drought and salt stress in this species. The expression patterns of 38 randomly selected DEGs were confirmed by quantitative real-time PCR and were essentially consistent with the changes in transcript abundance identified by RNA-seq. Conclusions The present study identified potential genes involved in drought and salt tolerance inC. korshinskii, as well as many DEGs uniquely expressed in drought- or salt-treatedC. korshinskii samples compared toArabidopsis . To our knowledge, this study is the first exploration of theC. korshinskii transcriptome under drought and salt conditions, and these results will facilitate the discovery of specific stress-resistance-related genes inC. korshinskii, possibly leading to the development of novel plant cultivars through genetic engineering.